Don't They Know it's Friday : Cross Cultural Considerations for Business and Life in the Gulf - Williams, Jeremy (Dubai, UAE Motivate Publishing, 1998)
Don't They Know it's Friday? has been the definitive guide to business culture and etiquette in the Gulf since it was first published in 1998. This exciting and informative book has been reprinted thirteen times. Motivate Publishing is now releasing a new edition fully updated with new information, maps and illustrations. This modern and enlarged second edition is packed with remarkable insights into Gulf life and business; the book is required reading for anyone having business and other interests in the GCC and in the wider Middle East. The book prepares its readers for many life-style changes. It addresses in particular the cross-cultural aspects of life affecting westerners and other nationalities in business with nationals in or from Kuwait, Saudi Arabia, Bahrain, Qatar, the UAE and Oman. It deals with the realities of Gulf business and outlines the stresses and strains which most visitors or expatriates will experience. Don't They Know it's Friday gives excellent guidance on proper behavior in the Arab world generally and in the Gulf particularly.
Include Illustrations, Appendix, Bibliography and Index.
Cross Cultural Considerations for Business and Life in the Gulf.
Keywords: Middle East--Persian Gulf Region -- Business etiquette -- Manners and customs -- Business enterprises -- Negotiation in business